Exploring the relationship between teaching methods and styles among educators / Zarith Sofiah Othman … [et al.] - Othman, Zarith Sofiah; Safiai, Suhalia; Mamat, Siti Salwana; Mohamad, Nor Azahariah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
The role of an educator in the contemporary educational landscape extends beyond information transmission, encompassing diverse teaching styles that shape student learning experiences. This study explores five distinct teaching styles: expert, authority, model, facilitator, and delegator, each with distinctive philosophies and methods. The background of the study emphasises the importance of understanding teaching styles in the Malaysian educational context due to diverse student backgrounds and the need for adaptable instructional methods. This quantitative study investigates the impact of direct, discuss, and delegate teaching methods on the teaching and learning processes while exploring potential relationships between these methods and teaching styles. The study participants include 100 educators, mostly females with advanced degrees in science and technology. The instrument in the study is a 5-point Likert scale survey with four sections to investigate the correlation between teaching methods and styles. The study identifies significant positive relationships between various teaching methods and styles, highlighting the interconnection of instructional strategies and educator behaviours. The findings emphasise the importance of flexible teaching strategies customized to meet the learners’ diverse needs. The implications of the study include improving teaching practices, encouraging student engagement, and promoting effective learning environments.